Analisis Fundamental Makro, Fundamental Mikro Terhadap Nilai Perusahaan dengan Struktur Kepemilikan, Kinerja Keuangan, Struktur Modal Sebagai Variabel Intervening pada Perusahaan Perbankan yang Terdaftar di Bursa Efek Indonesia Tahun 2019-2023 - Hidayati, Siti Nurul; Hwihanus (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET) - Lembaga KITA, 2024)
This study aims to examine the influence of macro and micro fundamental variables, ownership structure, and capital structure on financial performance and firm value in the banking sector-listed on the Indonesia Stock Exchange. The method applied is panel regression analysis by utilizing secondary data from 2019 to 2023. The independent variables studied include Non-Performing-Loans (NPL), Financing-to Deposit-Ratio (FZ), Loan to Deposit Ratio (LDR), inflation, GDP, and exchange rate as macro- and micro-fundamental indicators. Ownership structure variables, such as institutional and individual ownership, and capital structure variables such as Debt-to Asset-Ratio (DAR), Debt-to-Equity Ratio (DER), and Long-Term Debt-to Equity-Ratio (LDER) is also included in this analysis. The results showed that macro fundamental factors such as NPL, FZ, and LDR have a positive and significant influence on banking financial performance, as measured by Return on Assets (ROA), Return on Equity (ROE), and Operating Expenses to Operating Income (BOPO). However, their effect on firm value, as measured by Price-to Book-Value (PBV), Price-to-Earnings-Ratio (PER), and stock price, is not significant. In contrast, micro fundamental factors such as inflation, GDP, and exchange rates have a positive and significant impact on financial performance, but a negative and significant impact on firm value. In addition, institutional and individual ownership structures, as well as the firm's capital structure, also affect financial performance and firm value in different ways. This study emphasizes the importance of managing macroeconomic and microeconomic conditions for banking firms to improve financial performance and firm value in a sustainable manner.